Language Variations and Functions of Various Languages In Online Businesses On The Instagram Application: A Sociolinguistic Study - Nur Alifah; Irma Nuraeni Salsabila; Vika Fransisca (Syntax Literate, 2022)
the Covid-19 pandemic has caused many online businesses, one of which is the Instagram application. They post their sales on Instagram with various exciting captions. They use a variety of language variations as their promotion strategy and means of publication. This research aims to find variations in language and language functions in the captions of online business account posts on the Instagram application. This study uses a qualitative descriptive method with sociolinguistic studies: data collection techniques using listening and note-taking techniques. Language variants and maximizing the function of various languages ​​on the Instagram social media network are very effective and efficient. There are many variants of the function of various languages ​​in Instagram social media networks.